Linkages between Banks and Microfinance Institutions in Mali: A Case Study - Hans Dieter Seibel (Universität zu Köln, Arbeitsstelle für Entwicklungsländerforschung (AEF), 2005)
Mali, with a population of 11.7m, 70 percent rural, is located in the Sahel zone of West Africa. With a per capita income of US245 and a Human Development Index rank of 174, it is among the poorest countries in the world, highly vulnerable to external impacts.
Keywords: 330